Особливості емансипаційної функції ненормативної лексики у творчості Оксани Забужко і Анжели Картер - Клепуц, Л. (Літературознавчі обрії. Праці молодих учених, 2010)
The article deals with the specific function of the «bad language» which can be defined as a «language emancipation». The specific features of this function are examined. On the basis of the comparative analysis of the «Field Work in Ukrainian Sex» by Oksana Zabuzhko and «The Sadeian Woman» by Angela Carter some common and distinct traits of the language emancipation are emphasized.